Cognitive development Respiratory Tract Illness and Effects of eXposure (CORTEX) project: Combining high spatial resolution pollution measurements with individual level data, a methodological approach. (2018) - Rodgers, Sarah; Lyons, Jane; Mizen, Amy; Berridge, Damon; Akbari, Ashley; Carruthers, David; Davies, Gwyneth; Dearden, Lorraine; Doherty, Ruth; Lake, Iain; Mavrogianni, Anna; Milojevic, Ai; et al.
No abstract available